Eggshell Conductance and Incubator Humidity as Factors in Embryo Survival and Poult Growth - Christensen, V.L.; Wineland, M.J.; Ort, D.T.; Mann, K.M.; Neely, E.R. (International Journal of Poultry Science, 2006)
Eggshell conductance (G) and incubator humidity (RH) were hypothesized to affect poult embryo survival and hatchling growth. Nearly 4,000 fertilized eggs of the same weight were selected (within 2 standard deviations of the mean). Selected eggs were divided randomly between two incubators. One cabinet operated at 65% RH whereas the second operated at 50% RH, and both cabinets had the same temperature (37.2oC). At the completion of the 24th day of development, all eggs were weighed a second time to determine eggshell G. Three groups were formed at this time by calculating eggshell conductance and sorting into groups of eggs exhibiting high (Hi), average (Avg) or low (Low) G. The eggs were then placed in the same incubation cabinet for hatching. Measurements were made of embryo cardiac and intestinal physiology. Samples were collected at external pipping and hatching from each of the groups. Tissues were assayed for plasma glucose and lactate, cardiac and hepatic glycogen and lactate. The RH and G effects on survival were noted, and poult weights were recorded for the first 6 weeks of age. More embryos from eggs of Hi or Avg G survived than Low G eggs, but poults from Hi G eggs did not grow as well as those from Avg or Low G eggs. Low G poults showed depressed cardiac glycogen and elevated lactate and had less mature intestines. Thus, in the developmental process of turkey embryos, G and RH may determine organ maturity at hatching thereby influencing survival and growth.